Perbandingan Model Pembelajaran Team Assisted Individualization dengan Model Pembelajaran Two Stay Two Stray Terhadap Hasil Belajar Matematika - Indraswari, Nur Fitriyah; Hikmah, Maulidatul; Minggani, Fitriana (Musamus Journal of Mathematics Education, 2020)
The purpose of this study is to determine whether or not the differences in mathematics learning outcomes using the TAI learning model with TS-TS on functional derivative material. This research used a True-Experimental Design approach in the form of Posttest-Only Control Design. The population taken is all students of class XI-MIPA MAN Sumenep with sample class XI-MIPA 2 as experimental class I and class XI-MIPA 4 as experimental class II. The instrument used is in the form of TKAkh questions (Final Capability Test). Data analysis was performed using a t-test with a significance level of 5%. The results showed that the t-test is more than t-table, meaning that there were differences in mathematics learning outcomes using the TAI learning model and the TS-TS learning model on the functional derivative material